2016
DOI: 10.1080/09540121.2015.1131972
|View full text |Cite
|
Sign up to set email alerts
|

Gendered differences in the perceived risks and benefits of oral PrEP among HIV-serodiscordant couples in Kenya

Abstract: Pre-exposure prophylaxis (PrEP) is effective for preventing HIV among HIV serodiscordant heterosexual couples. Gender roles may influence perceived personal and social risks related to HIV prevention behaviors and may affect use of PrEP. In this study, interviews and focus groups were conducted with 68 individuals from 34 mutually disclosed serodiscordant heterosexual partnerships in Thika, Kenya. Socio-cultural factors that affect adherence to PrEP were explored using grounded analysis. Three factors were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 30 publications
4
30
1
Order By: Relevance
“…Carroll et al . examined gender dynamics within relationships and how these influence decision making relating to PrEP, identifying a wide variety of experiences . HIV‐negative women in their study overwhelmingly reported that the decision for either partner to initiate ART or PrEP, as appropriate, belonged entirely to their husbands.…”
Section: Resultsmentioning
confidence: 99%
“…Carroll et al . examined gender dynamics within relationships and how these influence decision making relating to PrEP, identifying a wide variety of experiences . HIV‐negative women in their study overwhelmingly reported that the decision for either partner to initiate ART or PrEP, as appropriate, belonged entirely to their husbands.…”
Section: Resultsmentioning
confidence: 99%
“…Although both women and men engage in agricultural production in western Kenya, for example, women are largely responsible for lesser-earning subsistence farming (African Development Bank 2007; Dalsgaard et al 2016). Indeed, 68% of the currently married women in western Kenya earn less money from paid work than their husbands (Kenya Ministry of Health and National Bureau of Statistics 2015) and are expected to perform unpaid work including childcare and cooking (African Development Bank 2007; Carroll et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, participants reported the need for women to use ART to prevent HIV transmission to the HIV-uninfected male partner so he could continue to provide financially for the family and care for the children. Others have documented how the sexual division of labour influences the uptake of biomedical HIV prevention strategies among serodiscordant couples (Carroll et al 2016; Fowler et al 2015). For example, men’s fear of side effects from PrEP, particularly influencing their ability to work and provide for their family, prevented them from accepting PrEP (Fowler et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Even then, this study did not document men’s reactions to receiving kits from their female partners. Given the gender imbalance between men and women particularly in sub-Saharan African countries – where men take the upper hand and control decision-making processes in the home [12] – the idea of using women to introduce HIVST kits to male partners can have adverse consequences for the women. This is particularly the case when such women deliver the kits without seeking the male partner’s consent first.…”
Section: Introductionmentioning
confidence: 99%